1997
DOI: 10.1128/mcb.17.2.760
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and Repair of Compound DNA Lesions (Base Damage and Mismatch) by Human Mismatch Repair and Excision Repair Systems

Abstract: Nucleotide excision repair and the long-patch mismatch repair systems correct abnormal DNA structures arising from DNA damage and replication errors, respectively. DNA synthesis past a damaged base (translesion replication) often causes misincorporation at the lesion site. In addition, mismatches are hot spots for DNA damage because of increased susceptibility of unpaired bases to chemical modification. We call such a DNA lesion, that is, a base damage superimposed on a mismatch, a compound lesion. To learn ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
133
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(143 citation statements)
references
References 63 publications
(84 reference statements)
7
133
2
1
Order By: Relevance
“…Such a mechanism has been proposed to explain the ability of another group of cisplatin adduct-binding proteins, the HMG proteins, to interfere with adduct repair (Huang et al, 1994). However, in a recent study, (Mu et al, 1997) reported that addition of the hMSH2/hMSH6 heterodimer to a cell-free excision repair system did not impair the ability of the nucleotide excision repair system to remove cisplatin adducts from DNA. The assay system utilized by these investigators measured only the excision nuclease activity in the absence of transcription, and the possibility of a negative interaction between the MMR and nucleotide excision repair systems in assays including transcription needs further investigation.…”
Section: Discussionmentioning
confidence: 89%
“…Such a mechanism has been proposed to explain the ability of another group of cisplatin adduct-binding proteins, the HMG proteins, to interfere with adduct repair (Huang et al, 1994). However, in a recent study, (Mu et al, 1997) reported that addition of the hMSH2/hMSH6 heterodimer to a cell-free excision repair system did not impair the ability of the nucleotide excision repair system to remove cisplatin adducts from DNA. The assay system utilized by these investigators measured only the excision nuclease activity in the absence of transcription, and the possibility of a negative interaction between the MMR and nucleotide excision repair systems in assays including transcription needs further investigation.…”
Section: Discussionmentioning
confidence: 89%
“…This low-level resistance was sufficient for enrichment of an MMR-deficient cell population in vitro (Fink et al, , 1998) and a reduced response of tumor cells in an in vivo model . Furthermore, purified MSH2 protein, either alone or in complex with its dimerization partner MSH6, can bind to oligonucleotides containing a cisplatin adduct (Duckett et al, 1996;Mello et al, 1996;Mu et al, 1997). Recently, the MMR proteins have been suggested to have a function as general sensors of DNA damage with the ability to signal directly to cell cycle checkpoints and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a gene dosage effect affecting the stoichiometry and the activity of the heteromolecular mismatch-repair complex may be sufficient to promote cancer by impairing functions other than the correction of replication errors. Mismatchrepair proteins are involved in a variety of vital cellular processes, including the homologous recombination (Jones et al, 1987;deWind et al, 1995), the mediation of the G2 checkpoint (Hawn et al, 1995), transcription-coupled nucleotide excision repair (Mellon et al, 1996) and in the recognition of DNA damage and/or in the signalling pathway contributing to the generation of apoptotic cells (Kat et al, 1993;Mu et al, 1997). Interestingly, the influence of environmental factors on the genome stability in cells defective in nucleotide excision repair and mismatch-repair could be substantial.…”
Section: Discussionmentioning
confidence: 99%